Autologous hematopoietic stem cell transplantation in patients with POEMS-syndrome: a literature review and own data - A. V. Popova; M. V. Solovev; A. V. Abakumova; N. K. Arutyunyan; M. V. Soloveva; A. A. Startsev; L. P. Mendeleeva (Онкогематология)
Background. POEMS‑syndrome is a rare lymphoproliferative disease accompanied by progressive polyneuropathy, which is the leading cause of deterioration in the quality of life and death of patients. Inclusion of autologous hematopoietic stem cell transplantation (auto‑HSCT) into the program therapy in somatically safe young patients is considered in order to achieve long and deep hematologic response and prevent disability. In the published literature, there are no data from large studies on the efficacy of auto‑HSCT in the therapy of such patients. Results of long‑term observations in patients who received auto‑HSCT as a consolidation phase of therapy provide an improved understanding of the efficacy of including high‑dose chemotherapy into program treatment.   Aim. To evaluate the efficacy of auto‑HSCT in the program therapy of patients with pOEMS‑syndrome.   Materials and methods. The medical records of 687 patients with plasma cell tumors over a 22‑year period (from 2001 to 2023) were retrospectively analyzed. A retrospective, single‑center study included 4 patients with pOEMS‑syndrome who received auto‑HSCT.   Results. After induction therapy, partial hematologic response (pR) has been achieved in 100 % of cases. According to vascular endothelial growth factor monitoring 2 patients showed pR, and 1 – complete response (CR). In 100 %of cases, there was a decrease in limb weakness, an increase in the mobility. On the 100th day of auto‑HSCT hematologic response was deepened to CR in 2 cases, 2 patients retained pR, at long‑term follow‑up – 3 CR and 1 pR. vascular endothelial growth factor response: 2 CR, 1 pR, in 1 case – an increase in marker concentration by 17.5 g / L from the upper limit of normal. On the 100th day of auto‑HSCT and at long‑term follow‑up (median 25.5 months) all patients showed further improvement of neurologic status on objective examination and electroneuromyography.   Conclusion. Auto‑HSCT provides high frequency of hematologic response, significantly improvement neurologic status and restoration of patients’ working capacity at long‑term follow‑up. The results of clinical studies, literature data, as well as the results of own observations confirm the efficacy of auto‑HSCT when this method is included into the program therapy of somatically safe young patients with pOEMS‑syndrome.